1979
DOI: 10.1121/1.383415
|View full text |Cite
|
Sign up to set email alerts
|

Transmission and reception of short ultrasonic pulses by circular and square transducers

Abstract: The transient fields of circular and square wide-band (1-5 MHz) ultrasonic transducers have been studied in water. Transmission and reception of short pulses have been observed using a small (150 pm) wide-band probe as both receiver and transmitter. Transmit-receive mode results from a small target have also been considered. Detailed comparisons with the theoretical waveforms for an ideal transducer (pistonlike in transmission and pressure-sensitive in reception) exhibit generally good agreement. The principle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
2

Year Published

1982
1982
2007
2007

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(16 citation statements)
references
References 0 publications
1
13
0
2
Order By: Relevance
“…The analysis of experimental results showed that field point waveforms and transmitter-receiver mode responses are in reasonable agreement with theoretical results calculated assuming ideal piston behaviour of the transducer [1,2]. These studies had also demonstrated the presence of the plane and edge waves in the radiated field [1][2][3][4][5][6].…”
Section: Generalized Spatial Pulse Response Function Approachsupporting
confidence: 60%
“…The analysis of experimental results showed that field point waveforms and transmitter-receiver mode responses are in reasonable agreement with theoretical results calculated assuming ideal piston behaviour of the transducer [1,2]. These studies had also demonstrated the presence of the plane and edge waves in the radiated field [1][2][3][4][5][6].…”
Section: Generalized Spatial Pulse Response Function Approachsupporting
confidence: 60%
“…Experimental observations of the pulsed field of a circular ultrasonic transducer have shown that measured fields are in good agreement with theoretical results, calculated assuming an ideal piston behavior. 4,5 These studies have also demonstrated that the radiated fields consist of plane and edge waves.…”
Section: Introductionmentioning
confidence: 94%
“…An example of pul sed wave propagat ion into a three layered system which includes Voigt-type damping is shown in Figure ( field is seen to be similar to that given by square ultrasonic transducers which include both plane and edge wave components [6]. The interaction of curved wave fronts with layers is further complicated in that mode-conversion is then important.…”
Section: Forward Models: Finite Differencementioning
confidence: 99%